Möbius-Hückel topology switching in an expanded porphyrin cation radical as studied by EPR and ENDOR spectroscopy - Möbius, Klaus; Plato, Martin; Klihm, Gudrun; Laurich, Christoph; Savitsky, Anton; Lubitz, Wolfgang; Szyszko, Bartosz; Stępień, Marcin; Latos-Grażyński, Lechosław (Freie Universität Berlin, 2015)
The symmetry of the arrangement of objects has fascinated philosophers, artists and scientists for a long time, and still does. Symmetries often exist in nature, but are also created artificially, for instance by chemical synthesis of novel molecules and materials. The one-sided, non-orientable Möbius band topology is a paradigm of such a symmetry-based fascination. In the early 1960s, in synthetic organic chemistry the interest in molecules with Möbius symmetry was greatly stimulated by a short paper by Edgar Heilbronner. He predicted that sufficiently large [n]annulenes with a closed-shell electron configuration of 4n π-electrons should allow for sufficient π-overlap stabilization to be synthesizable by twisting them with a 180° phase change into the Möbius symmetry of their hydrocarbon skeleton. In 2007, the group of Lechosław Latos-Grażyński succeeded in synthesizing the compound di-p-benzi[28 ]hexa-phyrin(1.1.1.1.1.1), compound 1, which can dynamically switch between Hückel and Möbius conjugation depending, in a complex manner, on the polarity and temperature of the surrounding solvent. This discovery of “topology switching” between the two-sided (Hückel) and one-sided (Möbius) molecular state with closed-shell electronic configuration was based primarily on the results of NMR spectroscopy and DFT calculations. The present EPR and ENDOR work on the radical cation state of compound 1 is the first study of a ground- state open-shell system which exhibits a Hückel–Möbius topology switch that is controlled by temperature, like in the case of the closed-shell precursor. The unpaired electron interacting with magnetic nuclei in the molecule is used as a sensitive probe for the electronic structure and its symmetry properties. For a Hückel conformer with its higher symmetry, we expect – and observe – fewer ENDOR lines than for a Möbius conformer. The ENDOR results are supplemented by and in accordance with theoretical calculations based on density functional theory at the ORCA level.